202 THE SILVER TRAUMA CLINIC—A MULTIDISCIPLINARY CLINIC FOR FRAIL OLDER PATIENTS FOLLOWING TRAUMATIC INJURY. (18th November 2021) - Ramiah, V; Byrne, C; Ramakrishnan, J; Morgan, P
Abstract: Background: Increasing numbers of older individuals are presenting to Irish emergency departments following trauma. Advances in the care of chronic diseases have increased the number of older people with active lifestyles, predisposing them to injury. 'Silver trauma' has been a relatively neglected despite deficits of traditional trauma care for this vulnerable cohort. The Silver trauma clinic was developed in conjunction with the Frailty Intervention Team, Geriatric services and HSCP service in May 2021. The goal of the clinic is to provide a comprehensive multidisciplinary management for frail older patients following non operative injuries. Methods: Frail older patients discharged from the ED can be referred for short interval multidisciplinary trauma review. A trauma tertiary survey is carried out by an emergency physician with specialist interest in geriatric trauma. Rapid access to imaging ensures timely definitive diagnosis. The service integrates virtually with specialist services, such as spinal orthopaedic services and musculoskeletal interventional radiology. Physiotherapists initiate a tailored early rehabilitation plan. Consultant geriatrician and frailty ANP screen for complications of injury as well as bone health, falls risk and cognitive screening. The clinic integrates with existing outpatient and community services for older persons. Results: The clinic has seen 30 patients since commencement in May 2021. Median patient age: 85. Injuries: 25% vertebral fractures, 30% limb fracture, 20% thoracic trauma, 30% pelvic trauma. Mean number assessments: 2. Disposition outcomes: Primary care 50%, Geriatric clinic 30%, Integrated Care Team 10%, specialist clinic 10%. Conclusion: The Silver trauma clinic is a new approach of patient focused multidisciplinary trauma care for frail older patients following non operative trauma in the Irish health system.